Modification of Financial Ratio Analysis Based on Fair Value: Is It More Predictive? - Nur Rahmanti Ratih; Marhaendra Kusuma; Yuniep Mujati Suaidah; Abdul Hadi Bin Ahamad (Jurnal Akuntansi dan Perpajakan, 2025)
The purpose of this study is to respond to these profit changes by modifying the ROA, ROE, and NPM ratio formulas by expanding the concept of "earnings" to include comprehensive income and attributable income. Observational data from 2,641 firm-years from 543 publicly listed companies in Indonesia for the 2020-2024 period using multiple linear regression analysis. The results of this study indicate that modified financial ratio analysis has value relevance because it influences stock returns and has predictive power over dividends. The implication of this finding is that profitability using comprehensive income has value relevance and that level 1 of the fair value hierarchy is the most predictive and most responded to by the market, compared to comprehensive income and attributable income. The originality of this study examines the value relevance of using modified financial ratio analysis, specifically profitability, by involving comprehensive income and attributable income.